A Validated HPTLC Method for Simultaneous Estimation of Lamivudine and Zidovudine in Tablets - B. Wankhede, Sagar; R. Gupta, Krishna; R. Tajne, Madhukar; G. Wadodkar, Sudhir (Asian Journal of Chemistry, 2010)
A validated high performance thin layer chromatographic method for simultaneous estimation of lamivudine and zidovudine in tablets is described. Aluminium plates precoated with silica gel 60 F254 were used as stationary phase and a mixture of toluene : methanol : nhexane (7 : 1.5 : 1.0) (v/v) as mobile phase. Quantitation was carried out by the use of densitometer in absorbance mode at 275 nm. Linearity of detector response for lamivudine and zidovudine was found in the range of 0.8-2.0 and 1.5-4.0 μg, respectively. Amounst of lamivudine and zidovudine estimated in the average weight of the tablet were found to be 149.09/148.12 and 301.41/300.74 mg (as per peak height/area), respectively. The per cent recovery for lamivudine and zidovudine was found to be 100.31/99.19 and 100.01/99.43% (as per peak height/area), respectively. The proposed method is accurate, precise, specific and reproducible and can be adopted for routine analysis of lamivudine and zidovudine in tablet formulation.